A direct current control strategy based on vector resonance controller for shunt active power filter. (July 2022) - Chen, Dongdong; Xu, Zhenming; Xiao, Long; Yan, Wenduan; Guo, Yinbiao
Abstract: From the perspective of complex vector, this paper derives the mathematical model of the three-phase three-wire shunt active power filter (SAPF) current control object, and based on it, derives the corresponding vector resonance control expression form coordinate transformation, and the steady-state accuracy, anti-interference ability, and stability of the system are analyzed. The deduction demonstrates the equivalence of the traditional detection load harmonic current control and the direct grid current control in this paper, and the consistency of the current regulator. Then, a direct vector resonance control structure of grid current based on the dq coordinate without detecting harmonic currents is designed, and the digital realization of the vector resonance controller, the adaptive ability to frequency, and the phase lag at the high-order control frequency are designed. And finally experimental verification under different working conditions is presented, the experimental results prove the practicability and effectiveness of the direct current control strategy based on the vector resonance controller proposed in this paper.